Adsorption characteristics of NH2-UiO-66 for the removal of hematite inorganic dye from industrial wastewater: Isotherm, thermodynamic, and kinetic study - Abbas Mohammadi; mehdi Sedighi (Journal of Hydraulic Structures)
Metal-organic frameworks (MOFs) have emerged as a class of highly promising materials for wastewater dye removal due to their unique properties. However, the existing body of research has primarily concentrated on the removal of organic dyes. To address this gap and contribute to advancements in water treatment technologies, this study investigates the efficacy of a zirconium- terephthalate-based MOF for the adsorptive removal of hematite, an inorganic dye, from aqueous environments. This investigation explored the influence of key parameters, including initial dye concentration, pH, adsorbent dosage, and adsorption temperature, on the adsorption capacity of NH2-UiO-66 for hematite. The findings revealed that elevated temperatures and initial dye concentrations promoted hematite adsorption onto NH2-UiO-66. Furthermore, the analysis of experimental data demonstrated concordance with the theoretical predictions of both the linearized Freundlich and Langmuir isotherm models. The study of kinetic models reveals that the pseudo-first-order model can adequately describe experimentally obtained data. The adsorption thermodynamic parameter ΔG0 was found to be approximately -3.70, -3.94, and -4.19 kJ.mol−1 at 298, 313, and 328 K, respectively. Furthermore, the ΔH0 and ΔS0 parameters were 5.15 kJ.mol-1 and 54.3 J.mol-1, respectively, indicating an endothermic adsorption mechanism. Further investigation found that the regeneration effectiveness is greater than 92% even after three adsorption cycles.